2021
DOI: 10.1177/2040622321995771
|View full text |Cite
|
Sign up to set email alerts
|

The role of pre-emptive Transjugular Intrahepatic Portosystemic Shunt in acute variceal bleeding: a literature review

Abstract: The development of portal hypertension has serious implications in the natural history of liver cirrhosis, leading to complications such as ascites, hepatic encephalopathy and variceal bleeding. The management of acute variceal bleeding has improved in the last two decades, but despite the advances in endoscopic methods the overall prognosis remains poor, particularly within a subgroup of patients with more advanced disease. The role of Transjugular Intrahepatic Portosystemic Shunt (TIPSS) is a well-establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, there is an estimated 15-21% risk of treatment failure or rebleeding in these patients, causing a rate of mortality as high as 80% [25]. In this perspective, TIPS placement in high-risk variceal bleeding patients (pre-emptive TIPS) has been clearly demonstrated to be superior to the standard medical treatment in improving survival [26][27][28][29]. A recent individual patient meta-analysis showed that preemptive TIPS significantly increased the proportion of high-risk patients with cirrhosis and acute variceal bleeding who survived for 1 year, compared with drugs plus endoscopy (hazard ratio (HR) 0.443; 95% CI 0.323-0.607; p < 0.001) [30].…”
Section: Tips Toward Liver Transplant: Role and Timingmentioning
confidence: 99%
“…However, there is an estimated 15-21% risk of treatment failure or rebleeding in these patients, causing a rate of mortality as high as 80% [25]. In this perspective, TIPS placement in high-risk variceal bleeding patients (pre-emptive TIPS) has been clearly demonstrated to be superior to the standard medical treatment in improving survival [26][27][28][29]. A recent individual patient meta-analysis showed that preemptive TIPS significantly increased the proportion of high-risk patients with cirrhosis and acute variceal bleeding who survived for 1 year, compared with drugs plus endoscopy (hazard ratio (HR) 0.443; 95% CI 0.323-0.607; p < 0.001) [30].…”
Section: Tips Toward Liver Transplant: Role and Timingmentioning
confidence: 99%
“…Patients with Child-Pugh class C (<14 points) or Child-Pugh class B (>7 points) with active bleeding or HVPG >20 mmHg during variceal bleed have a high risk of rebleeding and should be considered for the placement of pTIPS in 24-72 h. 10 pTIPS does not increase the risk of hepatic encephalopathy or worsening of ascites. 45 ACLF, HE, and hyperbilirubinemia at admission should not be considered as a contraindication for pTIPS as per the recent guidelines 10 (Figure 2).…”
Section: Variceal Hemorrhagementioning
confidence: 99%
“…For this reason, an accurate cardiac assessment becomes crucial in their evaluation before TIPS placement [34]. The correct evaluation of the right heart-pulmonary circulation unit could also be useful for the assessment of patient candidates for pre-emptive TIPS, where risk stratification appears to have a major impact on outcome [35].…”
Section: Current Guidelines For Tips Implantationmentioning
confidence: 99%